Efectos de la presencia de la banca extranjera en la banca nacional del Perú: un estudio comparativo 1995-2007 (avances) - Cortez Cortez, Gaby (2008)
The presence of foreign banks in the Peruvian economy is not a new phenomenon. However, its importance is reflected in the recent decades with the opening of the economy and the liberalization of the banking market. The purpose of this study is to assess the effects of foreign banks entry in the behavior of banks in Peru in relation to competition, efficiency, interest margin, and profit. We hypothesize that the foreign banks entry in Peru helps to stimulate domestic banks through greater competition, lower margins, reduced costs, increased efficiency and greater diversity of products and financial services.